Introducing problem-solving therapy training into Southwestern Ontario. Issue 1 (9th January 2017) - Marlatt, Nicole M.; Van Bussel, Elisabeth M.; Seitz, Dallas; Gutmanis, Iris
Abstract : Purpose: The purpose of this paper is to introduce problem-solving therapy (PST) training to an Ontario health region. The aim of this pilot project was to increase psychotherapy access by training community-based outreach clinicians and to understand their satisfaction with the training program as well as their confidence in applying the principles of PST. Design/methodology/approach: Clinicians from Southwestern Ontario who provide community-based mental health outreach services to older adults were invited to participate in this training opportunity. Selection was based on their existing client base, the geographic area they served, and self-reported foreseeable PST training benefits. Selected individuals received an eight-hour in-person didactic session, eight one-hour case-based learning opportunities, and individual case supervision. Acquired knowledge, perceived confidence in their skills, level of adherence to PST principles in clinical interactions, and satisfaction with the training program itself were measured. Findings: Of the 36 applicants, eight trainees were selected. All trainees completed their training and seven were successfully certified in PST. Trainees indicated a high level of satisfaction with the training experience. According to the evaluation tools, trainee confidence in providing PST significantly increased, though there was no statistically significant change in knowledge. Originality/value: This study provides the first evidence that PST can be introduced within a regional geriatric mental health service in Canada. The training involved both in-person training, web-based conferencing sessions and a supervisory component. The training lasted 16 hours and resulted in staff skill development in an evidence-based psychotherapy modality.